Behaviors of sliding bubbles in an inclinable turbulent channel flow investigated by optoacoustic measurement. (January 2023) - Yoon, Dongik; Park, Hyun Jin; Tasaka, Yuji; Murai, Yuichi
Highlights: Characteristics of wall-sliding bubbles inside turbulent channel flow. Buoyancy effect enhanced with increasing inclination and bubble size. Inclination is found to affect bubble shape and velocity. Drag coefficient quantified for sliding bubbles in turbulent boundary layers. Drag coefficient found to depend on bubble deformation, shape, and inclination. Abstract: Bubbles sliding in the vicinity of inclined walls are experimentally investigated to understand their fundamental behavior inside a turbulent boundary layer. A qualitative visualization confirms that the bubble shape varies with changes in channel inclination. An optoacoustic measurement technique is adopted to investigate the sliding motion of the bubbles. The diameters and advection velocities of individual bubbles are obtained from particle-tracking-type image processing, while the liquid velocity profiles in the bubbly flow and the maximum distance between the wall and bottom of the bubble are obtained using an ultrasound pulsed Doppler method. The combined measurement confirms that the effect of buoyancy on the slip velocity of the bubble is enhanced by an increase in inclination. Moreover, the drag and buoyancy determine the bubble shape in the inclined condition. The drag coefficient is derived from the measured variables using a force balance equation between drag and buoyancy, and we reveal that the drag coefficient increases with the inclination angle up to 35°. Finally, we propose a modeling equation for the drag coefficient in terms of the Weber number, inclination angle, and ellipticity of the bubble. This equation is applicable to bubbles inside turbulent boundary layers.